2022
DOI: 10.1136/rmdopen-2021-002055
|View full text |Cite
|
Sign up to set email alerts
|

Association between long-term exposure to air pollution and immune-mediated diseases: a population-based cohort study

Abstract: ObjectiveEnvironmental air pollution has been associated with disruption of the immune system at a molecular level. The primary aim of the present study was to describe the association between long-term exposure to air pollution and risk of developing immune-mediated conditions.MethodsWe conducted a retrospective observational study on a nationwide dataset of women and men. Diagnoses of various immune-mediated diseases (IMIDs) were retrieved. Data on the monitoring of particulate matter (PM)10 and PM2.5 concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…Their research area focuses on PM 10 having a positive association with autoimmune diseases, stating a risk of 7% is by an increase in 10 µg/m3. Risk of rheumatoid arthritis, an increase in PM2.5 exposure leads to inflammatory bowel diseases and connective tissue diseases (Adami et al, 2022 ). Air pollution exposure leads to respiratory or chronic diseases and disorders like psychiatric and schizophrenia, and depression.…”
Section: Text Mining Resultsmentioning
confidence: 99%
“…Their research area focuses on PM 10 having a positive association with autoimmune diseases, stating a risk of 7% is by an increase in 10 µg/m3. Risk of rheumatoid arthritis, an increase in PM2.5 exposure leads to inflammatory bowel diseases and connective tissue diseases (Adami et al, 2022 ). Air pollution exposure leads to respiratory or chronic diseases and disorders like psychiatric and schizophrenia, and depression.…”
Section: Text Mining Resultsmentioning
confidence: 99%
“…In contrast to the risk from silica exposure, the data from the EIRA study and NHS study did not show an association between estimated general exposure to fine particulate matter and the occurrence of RA [ 91 , 92 ]. However, in a nationwide Italian retrospective observational study of 81,363 subjects, a concentration-dependent association was detected between measured fine particulate matter exposure and the occurrence of autoimmune diseases [ 93 ]. The risk of developing RA was increased by exposure to particulate matter with a particle size of 10 µm or less and, even more significantly, to a particle size of 2.5 µm or less.…”
Section: Fine Particulate Mattermentioning
confidence: 99%
“…Although the idea that pollution contributes to disease is not new, there have been few cases where pollutants have been clearly linked to autoimmunity. However, a recent study following more than 80 thousand Italians showed a strong correlation between large particle (PM10) pollutants in the air and the incidence of RA, but not with psoriatic arthritis, lupus or MS ( 93 ). Here’s how the Danger model would put these data together.…”
Section: Codamentioning
confidence: 99%